Quality of life following thoracotomy for lung cancer - Debevec, Lučka (Radiology and oncology (Ljubljana), 2007)
Background. The aim of the study was to assess the preoperative and postoperative quality of life (QoL) in lung cancer patients undergoing thoracotomy and to compare the impairment of QoL in resected and exploratory thoracotomized (ET) patients. Patients and methods. Forty-three patients age 31 to 82 (mean 61) thoracotomized (lobectomy 29, bilobectomy 1, pneumonectomy 8, ET 5) for non-small cell lung cancer were assessed using the EORTC QLQ-LC30and QLQ-LC13 questionnaire preoperatively and a mean of 45 17 days after the thoracotomy and before eventual chemotherapy and radiation therapy. Results. After thoracotomy there were significantly impaired functional scales(physical functioning, role functioning, social functioning) and symptomscales (fatigue, constipation, appetite loss, dyspnoea, pain). The remaining symptoms (nausea/vomiting, insomnia, diarrhoea, coughing), global health status, functional scales (emotional functioning, cognitive functioning) and financial difficulties were impaired non-significantly. However, haemoptysis significantly improved and completely disappeared after thoracotomy. There were no significant differences between resected and ET patients. Conclusions. The study established significant impairment of QoL in the first two months after thoracotomy, but no significant differences betweenresected and ET patients.
Keywords: bolniki; kirurško zdravljenje; kvaliteta življenja; pljučni rak; rak (medicina)